Being Reasonable About Religion. - Charlton, William (Ashgate Pub., 2007)
When we start to discuss religion we run into controversial questions about history and anthropology, about the scope of scientific explanation, and about free will, good and evil. This book explains how to find our way through these disputes and shows how we can be freed from assumptions and prejudices which make progress impossible by deeper philosophical insight into the concepts involved. Books about religion usually concentrate on a few central Judaeo-Christian doctrines and either attack them or defend them with tenacious conservatism, yielding nothing. This book has a broader scope, and.